Screening and Molecular Identification of Phosphate-Solubilizing Rhizobacteria from Mangrove Ecosystem of the Lombok Island - Lalu Zulkifli; Prapti Sedijani; Dewa Ayu Citra Rasmi; Lalu Wira Zain Amrullah (Jurnal Biologi Tropis, 2020)
Phosphate solubilizing rhizobacteria can be used as a component in biofertilizer formulations to increase local and national food production without causing adverse risks to the environment compared to the use of chemical fertilizers. In this regard, screening and identification of phosphate solubilizing bacteria from the rhizosphere of several mangrove species that grow on the coast of Lombok Island has been carried out. The method of isolation used is the Pikovskaya method. Screening and identification activities have obtained 5 isolates of mangrove rhizosphere bacteria (BRM) which are indicated by their ability to form clear zones on Pikovskaya media, namely isolates BRM1 and BRM4 (isolated from the rhizosphere of Avicennia marina), BRM2 and BRM3 (isolated from the rhizosphere of Rhizophora apicullata), BRM5 (isolated from the rhizosphere of R. stylosa). All rhizobacteria isolates were identified as Gram-positive bacteria. Molecular analysis based on the comparison of 16S rRNA gene sequences of isolates with the genome database at GenBank (NCBI) using Mega 10 software, showed that all BRM isolates occupied the same cluster as bacterial species from the Genus Paenibacillus in the dendrogram of the phylogenetic tree, namely Paenibacillus sp. JWLB1 strain, Paenibacillus sp. Strain NO13, P. cineris strain cu1-7, P. favisporus strain CHP14, with genetic distance ranging from 1.3 to 1.4. Many species of the Genus Paenibacillus are currently known to play an important roles as plant growth-promoting bacteria. The BRM isolates obtained in this study can be further developed as a biofertilizer component (inoculant) in saline and dryland agriculture.